A Review of Platinum Diffusion in Silicon and Its Application for Lifetime Engineering in Power Devices. Issue 2 (20th November 2021) - Johnsson, Anna; Schmidt, Gerhard; Hauf, Moritz; Pichler, Peter
Abstract : In silicon power semiconductors, platinum is used to improve the switching characteristics of the devices by adjusting the lifetime of the minority charge carriers. Platinum diffusion in silicon has been a research topic for many scientists over the past decades. Herein, the current state of knowledge is presented together with the concepts developed for its use in silicon power devices. The relevant processes include diffusion from a platinum silicide, postimplantation annealing, and phosphorus‐diffusion gettering. The evaluation of corresponding experiments and the calibration of the models have not only resulted in more narrow limits for the equilibrium concentrations of vacancies and self‐interstitials in silicon and the transport capacity of interstitial platinum, but also in improved devices. Abstract : In silicon power semiconductors, platinum is used to improve the switching characteristics of the devices through lifetime adjustment of charge carriers. Platinum diffusion in silicon has been a research topic for many scientists over the past decades. Herein, the current knowledge on the topic of platinum diffusion in silicon is presented together with its utilization in silicon power devices.